Valero-Garcés, C. & Tipton, R. (2017). Ideology, ethics and policy development in public service interpreting and translation. Bristol & Blue Ridge Summit: Multilingual Matters - Liu, Lisheng (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
Book Review